Exosomal miRNAs in the plasma of Cynoglossus semilaevis infected with Vibrio harveyi: Pleiotropic regulators and potential biomarkers involved in inflammatory and immune responses - Zhu, Tengfei; Kong, Ming; Li, Chen; Shao, Changwei (Frontiers in Immunology, 2022)
Exosomes are a class of extracellular vesicles with diameters ranging from 50 to 150 nm. Incorporating diverse biological substances and being present extensively in biofluids, exosomes are involved in intracellular communication in various physiological and pathological processes and emerging as promising biomarkers for the prognosis and diagnosis of many diseases. Accumulating evidence shows that exosomes also play important roles in the inflammatory and immune responses to bacterial infection. However, the study of exosomes in teleost fish remains scarce. In the present study, we focused on the exosomal microRNAs (miRNAs) in the plasma of Chinese tongue sole (Cynoglossus semilaevis) in response to Vibrio harveyi infection. After bacterial challenge, the plasma was sampled at both the early (6 and 16 h) and late stages. (48, 72, and 96 h) of infection, followed by exosome isolation and exosomal miRNA sequencing. Results showed that the expression profile of 85 exosomal miRNAs was significantly different among the control, early-, and late-infection groups. The predictive genes targeted by exosomal miRNAs were extensively involved in various inflammatory and immune processes by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, suggesting that a series of processes were regulated by exosomal miRNAs in the plasma, including the pathogen invasion and recognition and the activation and regulation of signaling pathways related to cytokine production. Moreover, the spleen was found to be a preference for exosome enrichment and the underlying mechanism of interleukin-6 production regulated by ZC3H12A, ARID5A, and exosomal ssa-miR-146a-5p were probably present in Chinese tongue sole. Additionally, the enhanced levels of ssa-miR-146a-5p and nbr-miR-731 in plasma exosomes and the spleen of the infection groups were identified, indicating their application as biomarkers in favor of the prognosis and diagnosis of V. harveyi infection in Chinese tongue sole. Therefore, the collective results in the present study indicated the pleiotropic roles of exosomal miRNAs in the regulation of inflammatory and immune responses and their potential utilization as biomarkers in teleost fish.